No Allee effect detected during the natural recolonization by a large carnivore despite low growth rate. Issue 3 (25th March 2022) - Andrén, Henrik; Hemmingmoore, Heather; Aronsson, Malin; Åkesson, Mikael; Persson, Jens
Abstract: Eurasian lynx ( Lynx lynx ) have recently naturally recolonized southern Sweden. The first documented reproduction of lynx in recent times occurred in 2003, and the population increased from 2 to 48 family groups (the unit of measurement in Swedish monitoring) during its first 18 years (2003/2004–2020/2021). We did not detect any Allee effect, that is, lower growth rate at low population density, during the recolonization of southern Sweden, although our population simulations revealed a non‐negligible (30%) chance that population observed development could include an Allee effect. The probable absence of an Allee effect was likely because colonizing females did not lack mating partners, as a larger number of wide‐ranging males were established in the area before documented reproduction took place. Despite the absence of an Allee effect, the growth rate during recolonization was lower in southern Sweden ( λ = 1.20) than in central Sweden ( λ = 1.29). We have no evidence of higher mortality, including that from poaching, or lower reproduction in southern Sweden could explain the lower growth rate. Instead, we suggest that the lower growth rate during the recolonization of southern Sweden was explained by fewer immigrants arriving from central Sweden due to areas of less suitable habitat between central and southern Sweden, partially preventing immigration southward. From a conservation point of view, it is positive that this small population could recover without being negatively influenced by an Allee effect, as small populations with an Allee effect experience lower viability than those without.